Performance of oil based finishing materials on Sesenduk (endospermum diadenum) / Jahizah Syamim Mohamed Som - Mohamed Som, Jahizah Syamim (Faculty of Applied Sciences, 2016)
Finishing is an important process to decorate and the process is the last of a sequence of manufacturing actions. This study was being conducted to determine the finishing properties of Sesenduk (Endospermum diadenum) by using different types of coating varnish and nitrocellulose. Finishing also helps to enhance the aesthetic of the dimensional stability and durability. Oil based finishes have become most popular finishes used by woodworkers. So, all samples were being tested with two types of finishing testing and different application using brush, spray and rags. From this study, oil based shows good performance rather than varnish. Thus, wood working properties easy to saw and produces a smooth surface, nailing property is excellent